RoboCup rescue robot league - Pellenz, J.; Jacoff, A.; Kimura, T.; Mihankhah, E.; Sheh, Raymond; Suthakorn, J. (2015)
The RoboCup Rescue Robot League (RRL) aims to foster the development of rescue robots that can be used after disasters such as earthquakes. These robots help to discover victims in the collapsed structure without endanger the rescue personnel. The RRL has been held since 2000. The experience gained during these competitions has increased the level of maturity of the field, which allowed to deploy robots after real disasters, e.g. at the Fukushima Daiichi nuclear disaster. This article provides an overview on the competition and its history. It also highlights the current state of the art, the current challenges and the way ahead.